Comparative Effects of Er:YAG Laser, Sodium Hypochlorite, and QMix on Root Canals Infected With Enterococcus faecalis and Candida albicans: Antimicrobial Effect of Er:YAG Laser - Dragidella, Agime; Kameri, Ariana (Journal of Lasers in Medical Sciences, 2023)
Introduction: During endodontic treatment, the smear layer can reduce disinfectant efficacy. The aim of this study was to evaluate the antimicrobial efficacy of Er: YAG laser radiation and its combination with NaOCl and QMix against Enterococcus faecalis and Candida albicans and their comparison with conventional irrigation with only NaOCl and QMix. Methods: Two hundred extracted single-rooted teeth after root canal preparation were divided into two groups and inoculated with E. faecalis and C. albicans. According to the treatment method, all samples were divided into five treatment groups: (1) Er: YAG laser, (2) NaOCl, (3) QMix, (4) Er: YAG laser plus NaOCl, and (5) Er:YAG laser plus QMix. After 24 hours of agar plate cultivation, cell viability was recorded with a flow cytometer. Results: All treatment modalities showed efficiency in the reduction of microbial cells. For laser treatment alone after exposure for 90 seconds, significantly fewer non-death cells were seen, compared to 30-second treatment. For both timings (30 and 90 seconds), irrigation with NaOCl or QMix after laser application resulted in significantly fewer vital cells of E. faecalis and C. albicans, compared with laser treatment alone (P<0.001). The samples treated with only NaOCl showed a significantly higher percentage of vital E. faecalis and Candida albicans cells, compared to the samples treated with only QMix (P<0.001). Conclusion: Higher Er: YAG laser exposure time (90 seconds) after its combination with QMix and NaOCl improves the efficacy in the reduction of E. faecalis and C. albicans from the root canal, compared to 30-second laser exposure time and conventional irrigation methods with NaOCl and QMix.